Formulasi Pasta Buah Merah (Pandanus conoideus Lamk) dan Tepung Ubi Jalar Mikmak (Ipomea batatas L.) untuk Produksi Saus Buah Merah Pedas - Raden Haryo Bimo Setiarto; Nety Agustin; Rahmawati Rahmawati; Nunuk Widhyastuti; Albert Husein Wawo (Institut Pertanian Bogor, 2020)
Red fruit (Pandanus conoideus Lamk) and sweet potatoes (Ipomea batatas L) are the endemic plants that grow in the plains of Wamena, Papua. The processing of red fruit is very necessary to diversify food and increase its economic value. This study aims to determine the best formulation between red fruit paste, red chili pepper, and sweet potato flour to obtain spicy red fruit sauce product with a good nutritional quality and organoleptic properties. The formulation of red fruit paste and sweet potato flour was done with six levels i.e., A1 (100%:0%), A2 (95%:5%), A3 (85%:15%), A5 (80%:20%), and A6 (75%:25%). The quality of red spicy fruit sauce tested was physical quality (viscosity and total dissolved solids), chemical quality (and pH value), and organoleptic quality (hedonic test and hedonic quality with color, taste, flavor and consistency parameters). Based on the research, the best formulation was found in A2 treatment with the ratio of red fruit paste and sweet potato flour of 95%:5%. Formulation A2 has viscosity of 1733 cP, total dissolved solids of 21° Brix, pH value of 5.13, organoleptic value of color of 7.6, taste of 7.4, flavor of 7.4, and consistency of 6.6. The product of spicy red fruit sauce is in conformity with Standard National Indonesian (SNI 01-2976-2006) about chili sauce quality requirement on parameters of pH, viscosity, total dissolved solids, flavor, taste, color, and consistency. Keywords: formulation, Mikmak sweet-potato flour, red-fruit paste, spicy red-fruit sauce